2021
DOI: 10.31219/osf.io/jbzq4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“You Didn’t Cause Racism, and You Have to Solve it Anyways”: Antiracist Adaptations to Dialectical Behavior Therapy (DBT) for White Therapists

Abstract: There are currently no published studies that investigate or discuss the cultural responsiveness of Dialectical Behavior Therapy (DBT) to the needs of Black/African-American patients. In addition, no published scholarly works offer guidance to therapists on how to practice antiracism within the context of delivering evidence-based treatment. Methods for developing culturally responsive treatment are discussed within a dialectical framework. We propose that an antiracist adaptation to DBT is needed to correct f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As discussed above, invalidation—most simply defined as “a rejection of the valid” (Fruzzetti et al, 2005)—includes any actions or inactions that communicate to an individual that their responses do not make sense, and are not understandable within their current life context or situation (Linehan, 1993). An extremely common form of invalidation is well-meaning empathic failure (see Table 1; Fruzzetti & Vijay, 2020; Pierson et al, 2021); for example, families that value self-control and individual achievement may inadvertently invalidate a child who demonstrates age-appropriate weakness in self-regulation, while perfectionistic families may invalidate by placing high demands onto them and punishing expressions of intense emotion (Musser et al, 2018).…”
Section: Defining Invalidationmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, invalidation—most simply defined as “a rejection of the valid” (Fruzzetti et al, 2005)—includes any actions or inactions that communicate to an individual that their responses do not make sense, and are not understandable within their current life context or situation (Linehan, 1993). An extremely common form of invalidation is well-meaning empathic failure (see Table 1; Fruzzetti & Vijay, 2020; Pierson et al, 2021); for example, families that value self-control and individual achievement may inadvertently invalidate a child who demonstrates age-appropriate weakness in self-regulation, while perfectionistic families may invalidate by placing high demands onto them and punishing expressions of intense emotion (Musser et al, 2018).…”
Section: Defining Invalidationmentioning
confidence: 99%
“…However, because people are socialized into gender roles and heteronormativity early on, SGM individuals are often taught that their natural instincts (i.e., attraction to others of the same gender; understanding themselves as a different gender) are “wrong,” leading them to doubt themselves and their emotional signals from a young age (Proujansky & Pachankis, 2014). This, along with exposure to minority stressors, puts them at additional risk for forms of chronic and traumatic invalidation (e.g., internalized, abusive, systemic; Fruzzetti & Vijay, 2020; Pierson et al, 2021) on the basis of their SGM identities.…”
Section: Invalidation Of Sgm Peoplementioning
confidence: 99%
“…DBT is an evidence-based psychotherapy originally designed to treat individuals at high risk of suicide (Linehan, 1993) that has gained robust empirical support for treating borderline personality disorder (BPD; Storebø et al, 2020). Theoretical work suggests that the principles and structure of DBT may be well-suited to minoritized populations given its emphasis on the impact of invalidating environments on mental health and its core dialectic between acceptance and change (Chang & Cohen, 2022; Cohen et al, 2021; Pantalone et al, 2019; Pierson et al, 2021; Skerven et al, 2019; Sloan et al, 2017). Several studies have found that sexual minority people improved comparably to heterosexual people in various psychological and functional outcomes when participating in DBT for adolescents (Poon et al, 2022) and a cognitive behavioral therapy and DBT skills-based partial hospital program (Beard et al, 2017).…”
mentioning
confidence: 99%